Modifikasi Sistem Monitoring Data Universal Testing Machine Galdabini Type PM10 dengan Berbasis Arduino Uno - Sutrisno Sutrisno; Mery Lestari; Dovian Iswanda; Devi Andriani; Ahmad Faizal (Universitas Wahid Hasyim, 2023)
This study aims to repair damage to the Galdabini Type PM10 Universal Testing Machine (UTM) on a data acquisition system with an automatic system, design a conventional data acquisition system to a control system using the Arduino Uno AT Mega 328 microcontroller program and process the desired data and graphics with the help of the PLX application - DAQ Ms. Excel. This research uses the experimental method which is a basic framework used as a reference in conducting research which contains stages for solving problems in research. The research was conducted at the Materials Testing Laboratory of the Pontianak State Polytechnic Department of Mechanical Engineering by designing the input and output program for the PM10 Galdabini UTM data. In the tensile test, the output data displays force and addition data, a graph of the attraction and addition force relationship. While in Ms.Excel data obtained tensile stress, strain, modulus of elasticity, the proportion of changes in length and diameter, as well as a graph of the relationship between tensile stress and strain. In testing the compression output data displays force and shortening data, a graph of the compression and shortening force relationship. In Ms.Excel data obtained compressive stress, strain, modulus of elasticity, as well as a graph of the relationship between compressive stress and strain. In the bending test, the output data displays force and deflection data, a graph of the relationship between bending and deflection forces. In Ms. Excel, we get data on bending stress, modulus of elasticity, and graphs of the relationship between bending stress and deflection. Kata kunci: arduino uno, PLX-DAQ microsoft excel , universal testing machine.